2020
DOI: 10.1248/bpb.b19-01010
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Protects Renal Fibrosis through Activating the BMP-7-Smad1/5 Signaling Pathway

Abstract: Renal interstitial fibrosis (RIF) is a common pathological characteristic associated with end-stage renal disease. However, treatment strategies for RIF are still very limited. In this study, we reported that kaempferol, a classic flavonoid, exhibited strong and widely inhibitory effect on the expression of fibrosis related genes in transforming growth factor beta 1 (TGF-β1) treated NRK-52E cells. Further studies revealed that kaempferol inhibited TGF-β1 induced epithelial-mesenchymal transition (EMT) process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…[48][49][50] In pulmonary and renal fibrosis, BMP7 facilitates scar repair by regulating SMAD1/5. 51,52 In this study, we confirmed that the protein expression of BMP7 and phosphorylation of SMAD1/5/ 8 were significantly increased after both MenSCs and MenSCs-sEVs transplantation. Guo et al also indicated decreased expression of BMP7 and SMAD1/5 in the uterus of the IUA rat model, suggesting that BMP7 may be a potential target for IUA treatment.…”
Section: Discussionsupporting
confidence: 76%
“…[48][49][50] In pulmonary and renal fibrosis, BMP7 facilitates scar repair by regulating SMAD1/5. 51,52 In this study, we confirmed that the protein expression of BMP7 and phosphorylation of SMAD1/5/ 8 were significantly increased after both MenSCs and MenSCs-sEVs transplantation. Guo et al also indicated decreased expression of BMP7 and SMAD1/5 in the uterus of the IUA rat model, suggesting that BMP7 may be a potential target for IUA treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Although SB functions in a similar manner to GBE, GBE was significantly more effective than SB in reducing p-P38 MAPK, TGF-β1 and HIF-1α protein expression levels, as well as renal apoptosis, injury and fibrosis. This may be due to the fact that GBE contains multiple active ingredients (55), and several of these may exhibit anti-fibrotic effects via different pathways, including quercetin and kaempferol (56,57). Kaempferoll exhibits an inhibitory effect on TGF-β1-induced fibrosis related genes in renal tubular epithelial cells, and improves renal function in rats (58).…”
Section: Discussionmentioning
confidence: 99%
“…Some traditional Chinese drugs, such as Suctellaria baicalensis and Utrica dioica ( 24 ), as well as ginseng, have an inhibitory effect on TGF-β activity and can be used to alleviated symptoms of COVID-19 ( 25 ). Kaempferol, which can inhibit the secretion of mucus from goblet cells, is beneficial for the prevention and treatment of mucus hypersecretion of the lungs ( 26 , 27 ). Diterpene phenol extract of Rosmarinus officinalis has been reported to inhibit TGF-β in rats ( 28 ).…”
Section: Significance Of Clarifying the Feature Of Cytokine Stormmentioning
confidence: 99%